2013
DOI: 10.1371/journal.pone.0061769
|View full text |Cite
|
Sign up to set email alerts
|

Donor Safety in Living Donor Liver Transplantation: A Single-Center Analysis of 300 Cases

Abstract: AimTo evaluate the safety to donors of living-donor liver transplantation.MethodsThis study included 300 consecutive living liver tissue donors who underwent operations at our center from July 2002 to December 2012. We evaluated the safety of donors with regard to three aspects complications were recorded prospectively and stratified by grade according to Clavien’s classification, and the data were compared in two stages (the first 5 years’ experience (pre-January 2008) and the latter 5 years’ experience (post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 33 publications
3
55
0
3
Order By: Relevance
“…Parenchymal transection was performed with a minimum 1.0‐cm lesion‐free margin using the Cavi‐Pulse Ultrasonic Surgical Aspirator (CUSA, Valleylab, Boulder, CO). The procedure for the parenchyma transaction was similar to that of liver graft harvesting from living donors, which was introduced in our previous studies 24, 25. Notably, the left hepatic vein (HV), hepatic artery (HA), hepatic bile duct (HD), and the PV were carefully protected for subsequent reconstruction (Figure 1E).…”
Section: Methodsmentioning
confidence: 99%
“…Parenchymal transection was performed with a minimum 1.0‐cm lesion‐free margin using the Cavi‐Pulse Ultrasonic Surgical Aspirator (CUSA, Valleylab, Boulder, CO). The procedure for the parenchyma transaction was similar to that of liver graft harvesting from living donors, which was introduced in our previous studies 24, 25. Notably, the left hepatic vein (HV), hepatic artery (HA), hepatic bile duct (HD), and the PV were carefully protected for subsequent reconstruction (Figure 1E).…”
Section: Methodsmentioning
confidence: 99%
“…Although AST and ALT peaked on the first postoperative day in routine liver tests, bilirubin reached peak level on day 3 and it took 30 days to return to normal with PT. Lei et al [13] showed similar changes in liver tests in liver transplant donors. In our study, we followed liver test results for 3 days.…”
Section: Discussionmentioning
confidence: 78%
“…Результаты физического параметра и психологи ческого параметра настоящего исследования были схожи с данными зарубежных коллег [5][6][7][8][9][10], что подтверждает высокую безопасность для прижиз ненного донора операции резекции фрагмента пе чени в целях последующей трансплантации реци пиенту и эффективность опросника SF36 в оценке качества жизни родственных доноров фрагмента печени.…”
Section: заключениеunclassified